1985
DOI: 10.1203/00006450-198501000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sodium Nitroprusside on Blood Flow and Oxygen Delivery to the Organs of the Hypoxemic Newborn Lamb

Abstract: ABSTRACT. Vasodilators are used in newborns underconditions where hypoxia may be prominent. To study the effects of vasodilator therapy on organ oxygen delivery we measured blood flow (using radioactive microspheres) and arterial oxygen content in six chronically catheterized newborn lambs. Cardiac output and its distribution were measured during normoxia, hypoxia (10% O2 and 5% C02), and hypoxia with a nitroprusside infusion. Hypoxia decreased oxygen content but did not change heart rate, mean blood pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…RBF, renal vascular resistance and urine flow rate did not change significantly. In comparison with other immature animal species the newborn rabbit appears a valuable and inexpensive model for the study of acute hypoxemiainduced renal changes.Respiratory distress syndrome and birth asphyxia, hypoxemic conditions frequently encountered in newborn infants, can be asso ciated with an impairment in renal functions and renal failure [6,9,12,19,20], The pre cise role of hypoxemia in the absence of aci dosis and hypercarbia cannot be fully estab lished in human neonates [12] and has been assessed in neonatal animal models such as lambs [16,21,22,23], piglets [17] and pup pies [15]. However, the hypocarbia reported in some studies [15,17], as well as interspe cies variations and different experimental conditions could account for the discrepan cies reported in the literature.…”
mentioning
confidence: 99%
“…RBF, renal vascular resistance and urine flow rate did not change significantly. In comparison with other immature animal species the newborn rabbit appears a valuable and inexpensive model for the study of acute hypoxemiainduced renal changes.Respiratory distress syndrome and birth asphyxia, hypoxemic conditions frequently encountered in newborn infants, can be asso ciated with an impairment in renal functions and renal failure [6,9,12,19,20], The pre cise role of hypoxemia in the absence of aci dosis and hypercarbia cannot be fully estab lished in human neonates [12] and has been assessed in neonatal animal models such as lambs [16,21,22,23], piglets [17] and pup pies [15]. However, the hypocarbia reported in some studies [15,17], as well as interspe cies variations and different experimental conditions could account for the discrepan cies reported in the literature.…”
mentioning
confidence: 99%
“…In addition, we found no reported data on the effects of nitroprus-side on lambs as young as our newborn group of 0-3 d. However, several studies describe the cardiovascular effects in slightly older lambs. Mirro et al (17) studied the effects of nitroprusside on systemic blood flow and oxyen delivery in hypoxemic conscious lambs at age 5-7 d. They found, as we did in our newborn lambs, that cardiac output and systemic arterial pressure decreased in each of the lambs; however, the decrease in cardiac output was not statistically significant, possibly because of large variability and slightly older age. They noted that the combination of nitroprusside and hypoxia caused decreased oxygen delivery to the brain, kidney, and carcass.…”
Section: Resultsmentioning
confidence: 91%
“…Agents with predominantly P-adrenergic effects may increase right to left shunting by decreasing peripheral vascular resistance, whereas agents with predominantly a-adrenergic effects may decrease myocardial performance by increasing systemic vascular resistance (17). Whereas the general hemodynamic effects of these agents have been previously studied in both normoxic (18, 19) and acutely hypoxemic newborns (20), it is not known whether chronic hypoxemia alters the hemodynamic responses to those agents.…”
mentioning
confidence: 93%
“…The findings of the present study that hyp oxemia (Pa02, 15mmHg) did not signifi cantly alter small intestinal blood flow except in the jejunal mucosa (table III) is consistent with those of Edelslone and Holzman [ 1982], who found that moderate hypoxia (Pa02, 16 Torr) did not significantly change fetal intes tinal blood flow, however, a more severe degree of hypoxia (Pa02, 12 Torr) drastically reduced blood flow. In newborn lambs Nowicki et al [1984] and Mirro et al [1985] found no decline in intestinal blood flow dur ing hypoxemia. In contrast to the perinatal lamb, in adult animals arterial hypoxia in creased blood flow to the small intestine [Svanvik et al, 1968;Shepherd, 1978].…”
Section: Discussionmentioning
confidence: 99%